Coupled Orientation and Stretching of Chains in Mesoscale Models of Polydisperse Linear Polymers in Startup of Steady Shear Flow Simulations. Issue 2 (1st February 2016) - Gooneie, Ali; Schuschnigg, Stephan; Holzer, Clemens
Abstract : Polydisperse linear polymers are studied in startup of steady shear flow simulations using dissipative particle dynamics. The results show that with an increase in polydispersity the stress overshoot declines while the steady‐state stress increases. The broad relaxation response of polydisperse systems and the higher forces necessary to orient and stretch long chains in the flow direction result in these observations. Abstract : Polydisperse linear polymers are studied in startup of steady shear flow simulations using dissipative particle dynamics. The results show that with an increase in polydispersity the stress overshoot declines while the steady‐state stress increases. Various physical characteristics of the systems are studied including frequency of nonbonded interactions, gyration radius data, flow alignment angles, and average bond lengths. The patterns in the data suggest higher forces are necessary to orient and stretch long chain fractions in the flow direction. Relaxation modulus data prove the broad range of relaxation mechanisms in polydisperse systems. Linear viscoelasticity theory is used to quantify the relaxation spectrum. The results indicate an increase in the longest relaxation time in systems with higher polydispersity. The steady‐state shear viscosity results show higher viscosities with an increase in polydispersity at all shear‐rates. The good agreement of the characteristic behaviors of modeled polydisperse polymers with experiments is encouraging for future work.